Displaced women's opinion of the impact of forced displacement on their health (2006)
Objective: To nalyze the adaptation process of women internally displaced to the city and the relationship between dis placement and their self-perceived main health problems. Methods: A qualitative, exploratory, descriptive study was carried out by means of semi-structured individual interviews with a maximum variation sample of 25 internally displaced women. A narrative content analysis was conducted with mixed generation of categories and data segmentation by age and themes. The area under study consisted of five localities in the city of Bogotá (Colombia). Results: According to the interviewed women's discourses, their adaptation to city life depended on the new socioeconomic and environmental conditions and the psychosocial impact of displacement on the family. Precarious economic conditions forced them to live in an unhealthy environment and, occasionally, to adopt the role of head of household. In this role, many of these women, particularly young women, faced great difficulties in ensuring that the family's needs were met. Young women and teenagers reported behavioral changes due to displacement, including reproduction of violence in the home. The main self-perceived health problems among displaced women were mental health, access to food, infections and gynecological alterations. Displaced women identified the main factors hindering their access to health services as their economic situation and home responsibilities. Conclusions: Displaced women face new environmental and family challenges that negatively affect their health and access to healthcare. Specific interventions aimed at displaced women are required to foster better health through access to work and long-term socioeconomic stability.